Provision of Primary Healthcare Services in Urban areas of Bangladesh – the Case of Urban Primary Health Care Project - Alia Ahmad (Lund University, School of Economics and Management, Department of Economics, 2007)
Primary healthcare in Bangladesh is supposed to be a public responsibility, and until recently the government has tried to provide basic services directly through its own bureaucracy. However, the public sector faces acute problems in meeting the growing needs of urban population, especially the poor. In recent years, new institutions such as partnerships with not-for-profit private organizations are sought to improve the access and quality of primary care. This paper focuses on one urban partnership project, UPHCP in Bangladesh. It analyzes the accountability relationships among different stakeholders involved in the project and cost effectiveness of contracting out. The paper finds that the accountability relationships in UPHCP are not transparent, and the programme is costly in terms of human resources because of multiple principals and agents involved compared to direct government provision. The beneficial impact of UPHCP on urban primary care is well-documented, but such institutional arrangement will have difficulties in expansion on a large scale without external assistance. Another weakness of the programme is the lack of a sense of ownership and trust in its continuity among the population that works against social accountability and client power.
Keywords: I12; I18; 330; Contracting out; NGO's; Primary healthcare